Skin manifestation of gastric cancer (clinical case) - Yu. A. Dykhno; Yu. Yu. Vinnik; V. S. Tsykh (Современная наука и инновации, 2024)
Dermatological reactions are one of the most common manifestations of the paraneoplastic process. Paraneoplastic syndromes include non-oncological diseases that arise under the influence of hormones nd biologically active substances secreted by the tumor. In some cases, paraneoplastic syndrome allows the diagnosis of malignant neoplasm in the early stages, but, unfortunately, it can mask the tumor process with its pronounced manifestations, which leads to the late establishment of the true cause of the disease and belated special treatment. Description of the clinical case. This article will present clinical case of patient with dermatological reactions in gastric cancer. Patient P. 36 years old, complaints of pigmentation of the skin in the neck, armpits, inguinal region and elbow flexions; seizure-like it ching.Three years ago he received treatment for pityriasis versicolor. In this respect, he regarded the changes in the skin as a recurrence of the disease and decided himself used Comfoderm 2, Clotrimazole externally. Diagnosis: Papylar-pigment dystrophy of the skin (black acanthosis). The examination diagnosed Gastric C-r IIIc (T4aN3M0). Conclusion. With the aim of early detection of cancer, it is necessary to improve the qualifications of doctors in general medical care systems in matters of clinical symptoms and diagnostics of paraneoplastic syndrome.